Industrial strategies and policies managerial and entrepreneurial skills : under condition of global and regional chance ([ESCWA], 1995)
the formulation of new industrial strategies and policies by escwa countries.the global economy has undergone radical changes with important enterprises in developing countries particularly those of the escwa region.